DISKURSUS TEORETIS PENERAPAN GOOD GOVERNANCE DALAM FORMULASI KEBIJAKAN DAERAH - Simon Mote (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2020)
This study aims to describe and explore the connectivity of the concept of good governance in various sets of existing government theories, and contextualized in the process of policy formulation in the regions. The method used is literature study. This study found a very strong logical relationship between various theories of government and the theory of good governance. The concept of Good Governance is a derivative or part of the theory of governance, which emphasizes efforts to build governance based on community participation, rule of law, transparency, caring for stakeholders, oriented to consensus, equality, effectiveness and efficiency, accountability, and strategic vision. The prerequisites for the successful implementation of good governance include: participatory policy formulation, optimal regional institutional capacity, and transformative leadership in applying the principles of good governance. Keywords: Good Governance; Regional autonomy; Regional Policy